Taking adavantages of the cracked cape gooseberry fruit (uchuva: Physalis peruviana) to make marmalade - Alfonso, Delfina Rojas; Torres, Sonia Rocio Velandia; Sánchez, Adriana María Castro (Universidad Pedagógica y Tecnológica de Colombia, 2012)
Cape gooseberry growers association (ASOPROCIEN) has been created in Ciénega – Boyacà with fifty members. All fruit is sent to Andes Export Company without a postharvest handling and 20% of the production is returned to ASOPROCIEN because of the fruit cracking. A marmalade production line is being proposed during this study under a sensory evaluation and microbiological analysis, in order to obtain an innocuous product and in this way, take advantages of the production which is not freshly commercialized.